INCORPORATING THE PRINCIPLES OF CRITICAL DISCOURSE ANALYSIS IN A READING CLASSROOM - Yatmikasari, Ika (2012)
This thesis reports on the effectiveness of a teaching program on a reading subject which incorporated the principles of Critical Discourse Analysis (CDA). This study can be regarded as part of Critical Language Awareness (CLA), a pedagogical wing of CDA, since it infused CDA into a classroom practice. In this respect, this study examines the implementation of the principles of CDA in a reading subject, the effects it brings towards students' critical reading, and students' responses towards the teaching program. The study employed a qualitative case study which involved one class of English Department students at an Islamic university in Bandung. It used several data collection techniques including a phase of teaching in which the researcher acted as the participant observer, as well as students' reflective journals and questionnaire. Data from all sources reveal that the implementation of CDA's principles develops students' critical reading in general. It also demonstrates students' positive responses towards the teaching program that it gives plenty of new insights for them and improves their critical reading. All these results indicate that the infusion of CDA into the teaching of reading is considerably effective in enhancing students' critical reading.